The Construction of Digital Financial Ecosystems and Their Implications for Micro-Enterprise Financial Accessibility - Rukiah Rukiah; Azizatur Rahmah (Indonesian Journal of Enterprise Architecture, 2026)
This article examines how digital financial ecosystems shape micro-enterprise financial accessibility and identifies the dominant patterns emerging from recent studies on digital finance, financial inclusion, and micro-enterprise financing. The study employed a Systematic Literature Review guided by the PRISMA framework to ensure a structured, transparent, and traceable review process. Relevant literature was identified through Scopus and Google Scholar, covering publications from 2022 to 2026. Of 179 records initially identified, a staged process of screening, eligibility assessment, and inclusion resulted in 10 studies for final synthesis. The review shows that digital financial ecosystems generally improve micro-enterprise financial accessibility through digital payment systems, mobile-based financial services, and fintech-enabled mechanisms that reduce transaction costs, expand market reach, enhance financial visibility, and widen access to credit and other formal financial services. However, the findings also indicate that the impact of digital finance is not automatic, as its effectiveness depends on digital financial literacy, owner capability, trust, security, infrastructure quality, and institutional support. In addition, the synthesis highlights the role of data-based intermediation, particularly alternative credit scoring and digital transaction records, in reducing information asymmetry for micro-enterprises often excluded from conventional finance. Overall, this review contributes by consolidating fragmented evidence into an ecosystem-based understanding of financial accessibility and by emphasizing that meaningful inclusion requires the integration of infrastructure, data, capability, and governance.